A Handheld, Portable Image-Based System May Outperform Computer Navigation or Robotic Platforms in Providing Accurate Acetabular Component Positioning - Eric M. Slotkin, DO; Francesca Coxe, MD; Tristan Jones, BaSC, MPT, MBA; Thomas Morton, PA-C; Stefan Kreutzer, MD; Allejandro Della-Valle, MD (Arthroplasty Today)
Background: Malposition of the acetabular component during total hip arthroplasty (THA) is a leading cause of complications and need for revision. Robotic-assisted THA purports to improve accuracy of component positioning with many reports demonstrating over 92% of components within 10° of inclination and anteversion compared to intraoperative system output. This study aimed to evaluate the intraoperative accuracy output of acetabular cup position values using a handheld miniaturized portable navigation system (Naviswiss, AG) compared to postoperative computed tomography (CT) scans. Methods: A total of 108 direct anterior approach THA surgeries using the intraoperative navigation device were performed over a 6-month period. Intraoperative device output for measured acetabular component inclination and anteversion were recorded and compared with values derived from postoperative CT scans. Results: Postoperative CT analysis of acetabular component positioning demonstrated 97.22% and 94.44% were within 5° of intraoperative inclination and anteversion, respectively, compared to intraoperative values from the navigation unit. No CT demonstrated an absolute inclination or anteversion measurement difference more than 8° from the intraoperative navigation unit value. Overall, 92.59% of components were within 5° and 100% were within 8° for both inclination and anteversion compared to postoperative CT measurements. Conclusions: This handheld portable navigation system yielded highly accurate intraoperative component positioning values confirmed by postoperative CT scans during direct anterior THA, possibly superior to reported robotic-assisted THA values. These smaller, portable, and more accessible intraoperative units may provide surgeons improved accuracy and availability in a number of surgical settings for use in THA.